2015
DOI: 10.15406/mojor.2015.03.00104
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Factors for Shoulder Tendon Disorders 2015 Update

Abstract: Rotator cuff (RC) injuries have been classified as intrinsic when that tendon injury results from direct tendon overload, intrinsic degeneration, or other insult. RC injury mechanisms are Case Report AbstractEvidence for work-related exposure as a cause of shoulder tendinopathy is updated. Previous studies indicated that forceful movements combined with hands above head increases the likelihood of shoulder disorders. Hands above the shoulder and arm flexion or abduction at greater than 60° combined with forcef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
4
1
Order By: Relevance
“…The results of this study found that higher amounts of worker-rated peak force were associated with lower risk of neck/shoulder disorders, although confidence intervals were wide. This is inconsistent with previous findings, which found that increasing levels of force are associated with an increase in neck/shoulder disorders 11,14,18 . It is possible that the unexpected association is due to the large amount of missing data (>10%) for that exposure variable.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this study found that higher amounts of worker-rated peak force were associated with lower risk of neck/shoulder disorders, although confidence intervals were wide. This is inconsistent with previous findings, which found that increasing levels of force are associated with an increase in neck/shoulder disorders 11,14,18 . It is possible that the unexpected association is due to the large amount of missing data (>10%) for that exposure variable.…”
Section: Discussioncontrasting
confidence: 99%
“…This is inconsistent with previous findings, which found that increasing levels of force are associated with an increase in neck/shoulder disorders. 11,14,18 It is possible that the unexpected association is due to the large amount of missing data (>10%) for that exposure variable. More importantly, this inconsistent finding highlights the limitations of simply measuring peak force, without taking into consideration the posture during that force or the amount of time or the frequency exerting the force.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RC muscle fatigue is the primary cause of shoulder pathologies due to its direct influence on humeral and scapular kinematics [ 16 ]. In addition, the RC muscles experience increased mechanical stress during work-related tasks at elevation angles above 60° [ 17 ]. Muscle fatigue, experienced due to repetitive activities, tends to have a cumulative trauma effect over time, resulting in musculoskeletal disorders [ 6 ].…”
Section: Introductionmentioning
confidence: 99%